Pronounced haemodynamic changes during and after robotic-assisted laparoscopic prostatectomy: a prospective observational study. Issue 10 (5th October 2020) - Pawlik, Michael T; Prasser, Christopher; Zeman, Florian; Harth, Marion; Burger, Maximilian; Denzinger, Stefan; Blecha, Sebastian
Abstract : Objectives: Robotic-assisted laparoscopic prostatectomy (RALP) is typically conducted in steep Trendelenburg position (STP). This study investigated the influence of permanent 45° STP and capnoperitoneum on haemodynamic parameters during and after RALP. Design: Prospective observational study. Setting: Haemodynamic changes were recorded with transpulmonary thermodilution and pulse contour analysis in men undergoing RALP under standardised anaesthesia. Participants: Informed consent was obtained from 51 patients scheduled for elective RALP in a University Medical Centre in Germany. Interventions: Heart rate, mean arterial pressure, central venous pressure (CVP), Cardiac Index (CI), systemic vascular resistance (SVR), Global End-Diastolic Volume Index (GEDI), global ejection fraction (GEF), Cardiac Power Index (CPI) and stroke volume variation (SVV) were recorded at six time points: 20 min after induction of anaesthesia (T1), after insufflation of capnoperitoneum in supine position (T2), after 30 min in STP (T3), when controlling Santorini's plexus in STP (T4), before awakening in supine position (T5) and after 45 min in the recovery room (T6). Adverse cardiac events were registered intraoperatively and postoperatively. Results: All haemodynamic parameters were significantly changed by capnoperitoneum and STP during RALP and partly normalised at T6. CI, GEF and CPI were highest at T6 (CI: 3.9 vs 2.2 L/min/m²; GEF: 26 vs 22%; CPI: 0.80 vs 0.39 W/m²; p<0.001). CVP was highest at T4 (31 vs 7 mm Hg, p<0.001) and GEDI at T6 (819 vs 724 mL/m², p=0.005). Mean SVR initially increased (T2) but had decreased by 24% at T6 (p<0.001). SVV was highest at T5 (12 vs 9%, p<0.001). Two of the patients developed cardiac arrhythmia during RALP and one patient suffered postoperative cardiac ischaemia. Conclusions: RALP led to pronounced perioperative haemodynamic changes. The combination of increased cardiac contractility and heart rate reflects a hyperdynamic situation during and after RALP. Anaesthesiologists should be aware of unnoticed pre-existing heart failure to worsen during STP in patients undergoing RALP.